1998
DOI: 10.1086/306475
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Magnification of Population III Supernovae in Hierarchical Cosmological Models: Next Generation Space Telescope Perspectives

Abstract: We study the gravitational lensing magnification produced by the intervening cosmological matter distribution, as deduced from three different hierarchical models (SCDM, LCDM, CHDM) on very high redshift sources, particularly supernovae in protogalactic (Pop III) objects. By means of ray-shooting numerical simulations we find that caustics are more intense and concentrated in SCDM models. The magnification probability function presents a moderate degree of evolution up to z ≈ 5 (CHDM) and z ≈ 7 (SCDM/LCDM). Al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…Very rare and unique events, such as lensed supernovae (e.g. Marri & Ferrara 1998;Marri et al 2000), or a tidal disruption of a star by a BH (cf. Stern et al 2004) cannot be excluded either, but again such events are not expected to dominate the sample.…”
Section: C2 Transient Objectsmentioning
confidence: 99%
“…Very rare and unique events, such as lensed supernovae (e.g. Marri & Ferrara 1998;Marri et al 2000), or a tidal disruption of a star by a BH (cf. Stern et al 2004) cannot be excluded either, but again such events are not expected to dominate the sample.…”
Section: C2 Transient Objectsmentioning
confidence: 99%
“…As an example, we consider the so-called Standard Cold Dark Matter (SCDM), with Ω M = 1, Ω Λ = 0, and h = 0.5; the power spectrum |δ k | 2 is taken from Efstathiou et al (1992), normalized to the present-day abundance of rich clusters (σ 8 = 0.6; Eke, Cole, & Frenk 1996). To calculate the number density of dark matter halos as a function of redshift we use the Press & Schechter (1974, hereafter PS) formalism; this technique is widely used in semi-analytical models of galaxy formation and gravitational lensing (White & Frenk 1991, Kauffman 1995, Ciardi & Ferrara 1997, Baugh et al 1998, Guiderdoni et al 1998, Marri & Ferrara 1998 and it has been shown to be in surprisingly good agreement with the results from N-body numerical simulations. Given a power spectrum |δ k | 2 , one can write the Gaussian variance of the fluctuations on the mass scale M :…”
Section: Predictions For Cdm Modelsmentioning
confidence: 99%
“…We Ðnd that, even for sources at these early epochs, the optical depth for strong lensing is small, q B 0.008 for and SCDM. z s \ 7 Marri & Ferrara (1998) have recently explored in details the observational perspectives for Population III SNe detection with the NGST when gravitational magniÐcation is taken into account. They computed lensing frequencies and magniÐcation maps using a ray-shooting numerical technique and assuming pointlike lenses.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been realized by many authors (Kolatt & Bartelmann 1998 ;Metcalf 1999 ;Holz 1998 ;Marri & Ferrara 1998 ;Wang 2000 ; see also Linder, Schneider, & Wagoner 1988) that gravitational lensing of distant supernovae (SNe) may provide a new tool for doing cosmology. When corrected for light and color curve shapes, Type Ia SNe can be calibrated to be excellent standard candles, with a brightness at maximum B light of M V \ [19.4^0.15 mag (Riess, Press, & Kirshner 1996 ;Hamuy et al 1996).…”
Section: Introductionmentioning
confidence: 99%